2016
DOI: 10.1120/jacmp.v17i2.5819
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of anatomical change using a virtual proton depth radiograph for adaptive head and neck proton therapy

Abstract: The aim of this work is to demonstrate the feasibility of using water‐equivalent thickness (WET) and virtual proton depth radiographs (PDRs) of intensity corrected cone‐beam computed tomography (CBCT) to detect anatomical change and patient setup error to trigger adaptive head and neck proton therapy. The planning CT (pCT) and linear accelerator (linac) equipped CBCTs acquired weekly during treatment of a head and neck patient were used in this study. Deformable image registration (DIR) was used to register ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…It would also be desirable to explore robust optimization algorithms during plan optimization to simultaneously strive for a robust plan with optimal OAR sparing [25] [26]. Furthermore, with the development of fast and accurate dose calculation algorithms [27] and advanced online imaging analysis tools [28], application of adaptive proton therapy on HN treatment should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be desirable to explore robust optimization algorithms during plan optimization to simultaneously strive for a robust plan with optimal OAR sparing [25] [26]. Furthermore, with the development of fast and accurate dose calculation algorithms [27] and advanced online imaging analysis tools [28], application of adaptive proton therapy on HN treatment should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Digital radiography is the standard technology currently used in proton treatment centers. Cone-beam CT systems are beginning to be used in a few proton centers [32,33]. Batin et al [34] reported that surface imaging, such as AlignRT (Vision RT, Columbia, Maryland), may assist in the daily positioning of patients with breast disease.…”
Section: Image-guided Treatment Deliverymentioning
confidence: 99%
“…In recent years, IGRT techniques have been gradually catching up in proton therapy. CBCT has become available at some proton centers [13,14] and the use of surface imaging [15] has also been reported. Despite advanced alignment techniques, it is practically impossible to have a perfect alignment on every voxel, and residual setup errors persist.…”
Section: Introductionmentioning
confidence: 99%